Plant Reproductive Responses of Guava ‘Crystal’ Under Different Paclobutrazol and NPK Fertilizer Doses - Widyastuti, Raden Ajeng Diana; Pujisiswanto, Hidayat; Adeline Warganegara, Hayane; Sabeth Sutriana, Eli (Department of Agronomy and Horticulture, IPB University, 2023)
A preliminary study of the reproductive responses of crystal guava plants under varying doses of paclobutrazol and NPK fertilizer was conducted. The research took place in a small-scale ‘Crystal’ orchard in Rajabasa 1, East Lampung, from August 2021 to March 2022. The study employed a 3x3 factorial randomized complete block design, examining two factors: paclobutrazol and NPK fertilizer. The first factor, paclobutrazol (P), had three levels: 0 ppm (control), 2000 ppm, and 4000 ppm. The second factor, NPK fertilizer, was tested at three levels: 0 g per plant (control), 250 g per plant, and 500 g per plant. The key variables measured were the number of reproductive shoots, blooming flowers, and fruits, serving as indicators of the ‘Crystal’ guava plant's reproductive responses. The study findings recommended the application of 2000 ppm paclobutrazol and 500 g per plant of NPK fertilizer due to their significantly positive impact on increasing the number of reproductive shoots, blooming flowers, and fruits. Notably, there was no significant interaction observed between paclobutrazol and NPK treatments in regulating plant reproductive growth.